Adjusting Consumption Based Capital Asset Pricing Model within the Framework of an Open Economy: The Case of Iran - Bahrami, Jaber; Pahlavani, Mosayeb; Roshan, Reza; Rasekhi, Saeed (International Journal of Economics and Financial Issues, 2017)
The purpose of this study is to investigate the relationship of some macroeconomic variables and asset returns in the framework of a theoretical and empirical Consumption based Capital Assets Pricing Model (CCAPM); for this purpose, this relationship is investigated through the development of a CCAPM basic model and the importation of imported consumer goods in Epstein and Zin recursive utility function. The research sample consisted of eight portfolios and monthly data from 2003 to 2014. In the first phase, the designed pricing model parameters were estimated using Euler equations and the generalized method of moments (GMM) of Hansen and Singleton; estimation of Euler equations parameters indicates economic agents are patient and risk-averse, low elasticity of substitution between domestic consumer goods and imported consumer goods, and high intertemporal elasticity of substitution. In the second phase, impacts of exchange rate risk premium, inflation risk premium, market return risk premium, and consumption growth risk premium on asset premium were studied using Euler linear equations as asset pricing model and Fama-MacBeth two pass regression; results show that the exchange rate risk premium, inflation risk premium and market return risk premium have had a positive impact on asset premium, i.e. economic agents will have a demand for more premium reward in asset premium so as to have more risk appetite. Keywords: recursive utility, risk aversion, elasticity of substitution, CCAPM, GMM. JEL Classifications: C58, D81, G11, G12, G15.